Enhancing REDD+ Effectiveness in Indonesia Through Governance Reforms, Sustainable Finance, and Community Participation - Wally A. Sowe; Ebrima Ceesay (WISE Pendidikan Indonesia, 2025)
The global REDD+ framework designed to curb greenhouse gas emissions by reducing deforestation and forest degradation has become a central pillar of international climate mitigation efforts, particularly in tropical forest nations such as Indonesia. Despite its significant potential, the implementation of REDD+ in Indonesia continues to encounter systemic barriers that undermine its effectiveness. Key challenges include fragmented and weak governance systems, inconsistent and unpredictable financial support, unresolved land tenure arrangements, and the persistent exclusion of indigenous and local communities from meaningful participation in forest management. These structural limitations diminish the capacity of REDD+ to generate measurable and sustained climate benefits. This study provides an in depth examination of the institutional, socio-political, and economic obstacles that constrain REDD+ performance in Indonesia. It argues that the current project oriented and carbon-accounting–driven model must evolve into a more integrated governance architecture that aligns environmental conservation with livelihood security and equitable resource distribution. To strengthen REDD+ outcomes, the research advances several policy innovations, including the decentralization of forest governance, diversification of long-term financing pathways, recognition and protection of customary land rights, and systematic incorporation of local ecological knowledge. Enhanced monitoring, reporting, and verification (MRV) systems are also highlighted as essential for ensuring transparency and accountability. Insights from case studies in Central Kalimantan and West Papua further demonstrate that the durability of REDD+ initiatives hinges on community empowerment, clear land tenure arrangements, and reliable funding mechanisms. Together, these findings emphasize the urgent need to redesign REDD+ governance in Indonesia to ensure it functions not only as a climate mitigation instrument but also as a socially just and economically viable conservation strategy.